Study of the Physical Status of Children in Sensitive Periods of Their Development (Zien Journal of Social Sciences and Humanities, 2022)
The article presents the results of studies conducted to identify the level of physical development and motor fitness of preschool children. At the end of a preschool institution, it is necessary to take into account the individual characteristics of the physical status, as well as the regulation of physical activity corresponding to the biological needs of the children's body.